One-pot synthesis of sodium lauryl sulfate-loaded polyacrylonitrile solid-phase extractor for investigating the adsorption behavior of radioactive strontium(II) from aqueous solutions. (September 2020) - Mahmoud, Mamdoh R.; Hassan, Reham S.; Rashad, Ghada M.
Abstract: Sodium lauryl sulfate-loaded polyacrylonitrile (SLSLPAN) was synthesized in the present investigation using an in-situ one step process through gamma radiation-induced polymerization. The structure, composition, surface area and pore size and volume of the employed adsorbent were investigated by Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD) and nitrogen adsorption-desorption measurements. Adsorption of radioactive strontium(II) onto SLSLPAN was studied in the pH range 3–13. Batch kinetic data showed that the equilibrium was attained at 840 min and the pseudo-first-order was the best kinetic model for describing the kinetic data of the present adsorption process. The diffusion of strontium(II) into SLSLPAN was deeply studied using four diffusion models, namely, Bangham, Boyd, Weber-Morris and Mathewas-Weber models. Two-parameter (Freundlich, Langmuir and Temkin) and three-parameter (Redlich-Peterson, Toth and Generalized) isotherm models were used to analyze the adsorption equilibrium data of strontium(II) onto SLSLPAN. The maximum adsorption capacity calculated by the Generalized isotherm model is found to be 0.391 mmol strontium(II) per gram of SLSLPAN. The estimated mean free energy (E = 2.151 kJ/mol) indicated that strontium(II) radionuclides were physically adsorbed onto SLSLPAN. The value of enthalpy change (ΔH o = 35.325 kJ/mol) and those of free energy change (ΔG o = −15.278, −16.948, −18.619 and −20.288 at 303, 313, 323 and 333 K, respectively) confirmed that adsorption of strontium(II) radionuclides on SLSLPAN was endothermic and spontaneous process. Highlights: SLSLPAN was synthesized by gamma radiation-induced polymerization process. Adsorption behavior of strontium(II) radionuclides onto SLSLPAN was studied. Removal percentage of about 98% was achieved at the optimum conditions. Diffusion of strontium(II) into SLSLPAN was deeply studied. SLSLPAN exhibited adsorption capacity of 0.391 mmol strontium(II) per gram.